The Effect of the Expansion of the Voting Franchise on the Size of Government - Husted, Thomas A.; Kenny, Lawrence W. (Journal of Political Economy, 1997)
This paper examines the claim that expansion of the voting franchise has been an important factor in the growth of government. State government spending and state and local spending are explained using a panel of 46 states for 1950-88. Elimination of poll taxes and literacy tests led to higher turnout, particularly among the poor, and a poorer pivotal voter. As predicted, we find that these changes, a fall in the income of voters relative to state income, and the ouster of Republicans from state government led to a sharp rise in welfare spending but no change in other spending.